Perlindungan Hukum Nasabah Bisnis Trading dari Ketidaklayakan Pialang Berjangka Menurut Pasal 1365 KUH Perdata - Rifka Tunanga; Weny Almoravid Dungga; Mellisa Towadi (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
This writing aims to find out how the feasibility of futures broker PT. Forex family in managing the trading business and legal protection of customers of PT. Forex families. The method used in this paper is empirical normative method by collecting data through literature studies, interviews, and observation. The writing results show that agreements between futures brokerage companies and customers/investors in forex trading transactions are made in detailed and accurate standardized forms. In the transaction agreement, the contents are planned in advance by the parties to the futures brokerage company so that the customer/investor only has to agree to it if the customer is willing to accept the rules or terms and conditions that have been prepared and predetermined unilaterally by the futures brokerage company. Furthermore, the forex family conducts a forex investment business which in this case can be categorized as futures trading, so that in this case the license to carry out business activities must be granted by the competent authority, namely BAPPEBTI. Furthermore, in order to protect the interests of consumers and the public, the investment alert task force announced seven lists of illegal investment entities that were discontinued on November 3, 2021. One of the seven entities was named the FX family, which the task force called